Black people in post-colonial South Africa a genealogical analysis of dominant and plural narratives of black people in 20th-21st century - Wolff, Ernst (University of Pretoria, 2020)
Mini Dissertation (MA Social Science (African European Cultural Relations))--University of Pretoria, 2019.